The Effectiveness of Authentic Assessment Instrument Based on Higher Order Thinking Skills Integrated with Character Education - Ayuningrum, Nita Dwi; Ngazizah, Nur; Ratnaningsih, Arum (Journal of Innovation and Research in Primary Education, 2024)
This research aims to examine the effectiveness of the authentic assessment instrument based on Higher Order Thinking Skills (HOTS) integrated with character education on the theme "Heat and Its Transfer" to enhance the learning outcomes of fifth-grade students at SD Muhammadiyah Purworejo. A quantitative approach using the Quasi-Experimental method was employed, involving two groups: the control group and the experimental group. The authentic assessment instrument based on HOTS integrated with character education was implemented in the experimental group, while the control group used conventional assessment instruments. The results showed that the use of the authentic assessment instrument based on HOTS integrated with character education significantly improved the Higher Order Thinking Skills (HOTS) of the students. The average HOTS score in the experimental group was higher than that in the control group after the intervention. Furthermore, the use of this instrument also influenced the improvement of students' character. The analysis results demonstrated a significant improvement in the experimental group compared to the control group. Therefore, it can be concluded that the authentic assessment instrument based on HOTS integrated with character education is effective in enhancing HOTS and character of fifth-grade students on the theme "Heat and Its Transfer." This research has significant implications in the field of education, providing a foundation for the development of learning approaches that promote high-level thinking skills and students' character. It is recommended that this approach be implemented more widely in the learning processes of schools to support students' development in various aspects of learning.